Implementation of Interprofessional Education in Medical and Pharmacy Students with Year Differences: A Case Study - Wibowo, Ika Mulyono Putri; Setiawan, Eko; Wicaksono, Y. Adhimas Setyo; Kirtishanti, Aguslina; Dahliana, Anita; Susilo, Astrid Pratidna (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2025)
Background: Interprofessional education (IPE) is the foundation to prepare students for the core competencies to be an effective member of a healthcare professional team. The core IPE competencies include values and ethics, roles and responsibilities, interprofessional communication, and teamwork. Challenges occur when attempting to adopt IPE in the existing curriculum. While reports of IPE involving students with the same academic years have been documented, little is known about the feasibility to conduct IPE for students with different academic years in the settings without formal IPE courses.Aims: To explore students’ experience in implementation of IPE with different health disciplines and academic years.Case Discussion: Sixth year medical students and fourth year pharmacy students were invited to an online discussion session to reflect their experiences while collaboratively working on two health promotion projects in a Community Health Center. In addition, all teachers of the project participated in the discussion. The discussion was recorded, transcribed, and further analysed. Students showed mutual respect for each profession's role, learned from each other, and collaborated in preparing materials and implementing activities. Extensive discussions with teachers are a key component of the implementation. Differences in academic year did not impede implementation.Conclusion: This case study shows that IPE involving students with different academic years is feasible without jeopardising the attainment of the core IPE competencies. Experiential learning through health promotion projects can be an effective approach for IPE in the settings where IPE is an add-on program in the existing curricular.